Entrepreneurship as a dynamic field of study: a bibliometric analysis of research output - Luis Javier Cabeza Ramírez; Sandra Mª Sánchez Cañizares; Fernando J. Fuentes García (Tourism & Management Studies)
The present study’s objective was to carry out a systematic literature review whose main value lies in updating and analysing the current state of scientific production in the field of entrepreneurship based on the best known international bibliographic databases, Web of Science and Scopus. To this end, the relevant papers published in indexed international journals were selected from both databases. The most-cited research was identified by setting a standardised threshold number of citations based on the Hindex called ‘H-Classics’, which is sensitive to the particular characteristics of each research area. This study analysed the most important authors, years of greater production, journals, cited authors, themes, subject areas, text typology, countries, institutional affiliations and keywords. The results are rankings of journals and authors based on the weights given by both databases’ H-index for citation frequency.